Exploring the feasibility and acceptability of a mixed-methods pilot randomized controlled trial testing a 12-week physical activity intervention with adolescent and young adult cancer survivors - Wurz, Amanda; Brunet, Jennifer (Université d'Ottawa | University of Ottawa, 2019)
Background: Adolescent and young adult (AYA) cancer survivors (i.e. individuals diagnosed with cancer between 15 and 39 years and who completed treatment) may benefit from physical activity. Yet, few researchers have explored the effects of physical activity on physical and psychological outcomes among AYA cancer survivors. A pilot study exploring the feasibility and acceptability of a physical activity intervention and proposed trial methods to inform a definitive randomized controlled trial (RCT) is therefore necessary to fill this gap. Methods: A two-arm, mixed-methods pilot RCT was conducted. Participants were randomized to a wait-list control group or a 12-week physical activity intervention comprised of 4 weekly aerobic and strength training sessions (intervention group). Feasibility measures included: number of AYA cancer survivors referred/self-referred, eligible, and recruited, retention to the trial (i.e. assessment completion), adherence to the physical activity intervention, and percentage of missing data for baseline (week 0), mid- (week 6), and post-intervention assessments (week 12). The acceptability of trial methods (all participants) and the intervention (intervention group only) was assessed via qualitative interviews post-intervention. Results: Over a 12-month period, 31 AYA cancer survivors were referred/self-referred and 16 were eligible and consented to participate. Retention to the trial was 94% and adherence to the physical activity intervention ranged from 50 to 92%. With the exception of the assessment of aerobic capacity and directly measured physical activity behaviour, there were no missing data. Participants generally reported being satisfied with the trial methods and intervention; however, issues related to delivery of the physical activity intervention were identified. Conclusions: The methods and intervention piloted require modification and further pilot testing in advance of a definitive RCT. Recruitment strategies identifying a greater number of younger AYA cancer survivors who have different types of cancers and who lack motivation to participate in physical activity-based studies should be explored. Refining the assessments of directly measured physical activity behaviour and aerobic capacity and incorporating behavioural support into the intervention may improve feasibility and acceptability. This study highlights the value of doing pilot work and provides critically useful data that can be used to refine studies seeking to assess causation and optimize physical activity interventions for AYA cancer survivors.
Keywords: Adolescent and young adult; Oncology; Exercise; Feasibility; Acceptability; Pragmatic approach